COP 27 CA side event presented in Morocco pavilion in Egypt - Moussadek, Rachid; Nangia, Vinay; Govind, Ajit; Nkomo, Mandlenkosi (2023)
Transformative Climate Adaption In Morocco 1 M Ha Conservation Agriculture Project In Morocco Under the New Generation Green Agricultural Strategy (2020-2030) was held in Morocco in November,2022